2019
DOI: 10.1002/jper.18-0004
|View full text |Cite
|
Sign up to set email alerts
|

Catechin ameliorates Porphyromonas gingivalis‐induced inflammation via the regulation of TLR2/4 and inflammasome signaling

Abstract: Background: Porphyromonas gingivalis is a major periodontopathogen found in patients with chronic periodontitis that can lead to alveolar bone or tooth loss. Interleukin-1 (IL-1 ), a proinflammatory cytokine, is most relevant to the pathogenesis of periodontitis. Catechin is one of the main polyphenol compounds found in green tea and possesses a range of health benefits. This study examined the antiinflammatory effects of catechin in THP-1-derived macrophages infected with P. gingivalis as well as its effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The anti-inflammatory activity of açaí is often associated with the presence of flavonoids, such as catechin and epicatechin, both in the pulp fruit [ 18 ] and in the seeds [ 19 ]. Catechin’s anti-inflammatory effect is well described alone, acting via the regulation of Toll-like receptor (TLR) 2/4 and inflammasome signaling [ 20 ], or in combination with other compounds, suppressing the production of inflammatory cytokines in mouse macrophages in vitro in association with baicalin and β-caryophyllene [ 21 ], and inhibiting the activation of TLR4-MyD88-mediated nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and mitogen activated protein kinase (MAPK) signaling pathways in RAW 264.7 macrophages in association with quercetin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory activity of açaí is often associated with the presence of flavonoids, such as catechin and epicatechin, both in the pulp fruit [ 18 ] and in the seeds [ 19 ]. Catechin’s anti-inflammatory effect is well described alone, acting via the regulation of Toll-like receptor (TLR) 2/4 and inflammasome signaling [ 20 ], or in combination with other compounds, suppressing the production of inflammatory cytokines in mouse macrophages in vitro in association with baicalin and β-caryophyllene [ 21 ], and inhibiting the activation of TLR4-MyD88-mediated nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and mitogen activated protein kinase (MAPK) signaling pathways in RAW 264.7 macrophages in association with quercetin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The green tea extract showed higher activity than black tea extract. Other studies have confirmed the inhibitory effect of flavan-3-ols obtained from tea on the secretion of pro-inflammatory cytokines from LPS stimulated macrophages as well from cytokines-stimulated gingival cells (table 1), [14], [23], [24], [35]. Ben Lagha et al [20] presented consistent results in which they proved inhibitory effect theaflavins (TFs) from black tea on the secretion of pro-inflammatory cytokines from P. gingivalis-treated macrophages and on the activation of the NF-κB signaling pathway (table 1).…”
Section: Influence On Cytokinesmentioning
confidence: 61%
“…IL-1β) can be mediated via signaling cascades, including NF-κB and MAPK/AP-1 pathways, which lead to gene expression of certain proteins (for example IL-6). There are more and more studies proving that proanthocyanidins and flavan-3-ols inhibit the secretion of cytokines by influencing NF-κB and MAPK/AP-1 activation (table 1), [14], [13], [18], [19], [20], [22], [37], [26], [28]. Many studies have shown inhibition of production and / or secretion of inflammatory cytokines by proanthocyanidins.…”
Section: Influence On Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such, in mice suffering from periodontitis induced by Porphyromonas gingivalis, downregulation of NLRP3 and AIM2 inflammasome activation was observed. Catechin also suppresses the production of IL-1β by inhibiting pro-IL-1β expression via the downregulation of nuclear factor-κB, p38 mitogen-activated protein kinase, and TLR signaling in THP-1 cells [ 117 ]. Similarly, subcutaneous injection of catechin decreases monosodium urate (MSU)-induced IL-1β and IL-6 secretion in C57BL/6 mice ( in vivo ) and inhibits MSU-induced IL-1β secretion, intracellular calcium and NLRP3 inflammasome activation in MSU-challenged THP-1 cells ( in vitro ) [ 118 ].…”
Section: Substances That Can Inhibit Inflammasome Activitymentioning
confidence: 99%